Fracture Incidence, Quality of Life, and Back Pain during 18-Months Treatment with Teriparatide in Greek Postmenopausal Women with Osteoporosis: Results from the European Forsteo Observational Study - K. Aloumanis; D. Karras; V. Drossinos; E. Korelis; A. Polydorakis (Journal of Osteoporosis)
Objective. To evaluate fracture incidence, effects on health-related quality of life(QoL), back pain (BP) occurrence and treatment compliance in Greek post-menopausal osteoporotic women treated with teriparatide (TPTD) for up to 18 months, in a naturalistic setting. Methods. 301 patients provided baseline information on demographic characteristics, fracture history, osteoporosis-related medication and risk factors. During treatment, QoL and BP severity were evaluated. Results. Mean (SD) age was 69.5 (±8.5) years. Fracture history was reported by 92.5% of patients. Incidence of fractures (per 10,000 patients/years) ranged from 402 during 0–6 months of treatment, to 346 during 12–18 months. All 5 dimensions of QoL showed improvement. At baseline and 18 months, BP was reported by 93.2% and 64.2% of patients, respectively. BP and limitation of activities were quantified as moderate or severe by 89.9% and 62.3% of patients at baseline versus 32.4% and 14.8% at 18 months. Patients on treatment at 6, 12, 17, and 18 months were 92.6%, 88.3%, 79.6%, and 36.5%, respectively. Conclusions. In the Greek EFOS study cohort, patients prescribed TPTD were severely osteoporotic, with considerable health-related problems. Significant improvements in QoL and BP together with low fracture rates and high compliance have been recorded during treatment.